KORELASI ANTARA PEMAHAMAN KITAB SAFINATUN NAJAH DENGAN PRAKTIK IBADAH SHALAT SISWA KELAS VIII MTs MA'ARIF GONDANG WATUMALANG - Sofiyatul Mukaromah; Nurul Mubin; Muhammad Saefullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The objectives of this research are: 1) To determine the students’ understanding of the book Safinatun Najah in grade VIII at MTs Ma’arif Gondang; 2) To assess the students’ practice of prayer in relation to their understanding of the book Safinatun Najah; 3) To identify the correlation between the understanding of Safinatun Najah and the students’ practice of prayer.This study is a field research using a quantitative correlational approach. Data collection techniques include observation, testing, and documentation. To test the hypothesis, the researcher used the Product Moment correlation formula. The sampling technique used was total sampling, where the number of samples equals the population, namely 68 students.The results of the study show that: (1) The understanding of Safinatun Najah among grade VIII students at MTs Ma’arif Gondang Watumalang falls into the “good” category with an average score of 78.27; (2) The result of the prayer practice test for grade VIII students at MTs Ma’arif Gondang Watumalang also falls into the “good” category with an average score of 88.11; (3) The correlation result between the understanding of Safinatun Najah and prayer practice shows a Product Moment test score of 0.389 with a significance level of 0.001. This is proven by the empirical correlation coefficient (r-count) = 0.389, which is greater than the Pearson Product Moment table coefficient at the 5% significance level = 0.2387 and at the 1% significance level = 0.3104. Thus, the hypothesis proposed by the researcher is accepted, namely “there is a positive and significant correlation between the understanding of the book Safinatun Najah and the practice of prayer among grade VIII students of MTs Ma’arif Gondang Watumalang.”